Endoscopic Brow Elevation and Reshaping - Plowes Hernandez, Olga; Montes-Bracchini, Jose Juan; Ulloa, Fausto López; LaFerriere, Keith (Facial Plastic Surgery, 2016)
One of the first signs of aging belongs to the upper third of the face. At the same time, the height and shape of the eyebrows are key points of the periorbital aesthetics. A “tired” or “sad” look implies that the complex eyebrow–upper eyelid are showing one or more of these signs. Different surgical techniques as well as nonsurgical have been described to treat this area, every one of them aiming at making the patient look rested and natural. The objective of this study is to describe a technique for endoscopic browlifting, consisting of minimal incisions, a biplanar dissection, and a different fixation technique designed for helping reshape the brow. Twenty-five patients who fulfilled the criteria for the study were analyzed for brow-position changes in height and shape. All the patients were treated by the senior authors using the technique described. This particular surgical technique has shown the advantage of being minimally invasive and effective. Careful analysis of the patient should be made to decide both the technique and the changes desired by the patient and the surgeon. The authors believe the technique described is another option for approaching and fixating the eyebrow.
Keywords: endoscopic; eyebrows; fixation